Experimental Study of Novel Polycarboxylate-Based Superplasticizer for Concrete - Zeng, Fankui (Asian Journal of Chemistry, 2014)
As a result of the rapid development of construction industry, plasticizers have been widely required in various cases. However, disadvantages such as high cost and complicated synthesis process have limited the large-scale application of current superplasticizers. In this article, we report an experimental study of polycarboxylate-based high performance superplasticizer. By using distinctive process, feedstock and ratio, carboxylic group was added to the molecules of amino sulfonic-based superplasticizer and a novel polycarboxylate-based superplasticizer was synthesized. The results revealed that both low cost and high performance (water reduction rate = 45 %) were achieved, indicating that this novel plasticizer can be applied in high performance concrete. Moreover, ready-mixed concrete by this plasticizer showed a slump loss less than 15 % in 2 h, which enables long distance transportation and pumping.